The efficacy and safety of targeted narrowband UVB therapy: a retrospective cohort study - SALMAN, ANDAÇ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: Phototherapy is a safe and effective treatment modality for numerous dermatological conditions. Recently, targeted phototherapy modalities have gained importance due to their advantages over conventional phototherapy. This retrospective study aimed to evaluate the safety and efficacy of targeted narrowband UVB phototherapy in patients with dermatological disorders. Materials and methods: This single-center study included 173 patients who were treated with targeted narrowband UVB phototherapy. Demographic features, phototherapy parameters, and adverse effects were evaluated in all patients, and the treatment response was assessed in patients who attended at least one follow-up visit. Results: A total of 173 patients (102 females; 71 males) with vitiligo, alopecia areata, lichen simplex chronicus, palmoplantar psoriasis, and psoriasis vulgaris were included in the study. Among 73 patients, with whom the treatment was finalized by physician, an excellent response was obtained in 10%, 52.9%, 53.8%, 28.6%, and 40% of patients with vitiligo, alopecia areata, lichen simplex chronicus, palmoplantar psoriasis, and psoriasis, respectively. The treatment was generally well tolerated and was discontinued in only two patients due to adverse effects. Conclusion: This study demonstrates that targeted narrowband UVB therapy is a safe and effective treatment alternative, particularly for alopecia areata, lichen simplex chronicus, and palmoplantar and plaque-type psoriasis.
Keywords: Alopecia areata; lichen simplex chronicus; psoriasis; targeted phototherapy; ultraviolet B; vitiligo; ULTRAVIOLET-B PHOTOTHERAPY; PLAQUE-TYPE PSORIASIS; TOPICAL 8-METHOXYPSORALEN; ALOPECIA-AREATA; VITILIGO